Antibacterial Activities of Oregano- N-acetyl cysteine Nanocomposite against Multidrug-resistant Riemerella anatipestifer Isolated from Ducks - Eid, Samah; Hashem, Yousreya; Al-Atfeeh, Nayera M.; Baz, Heba A.; Mwafy, Abeer; Elmasry, Dalia M.A. (Journal of Advanced Veterinary Research, 2023)
Riemerella anatipestifer (R. anatipestifer) considered a highly epizootic pathogen, causes (duck septicemia) resulting in significant ducklings mortality and surviving birds may grow poorly leading to significant worldwide economic losses in the duck industry. As emerging of extensive multidrug resistance strains of R. anatipestifer, alternative treatment is of great concern for R. anatipestifer control. During (January - August 2020), different outbreaks in 20 suspected field duck farms, and 6 R. anatipestifer isolates which were confirmed by conventional PCR technique underwent an in vitro study. The isolates were tested against 17 antimicrobial agents (widely used in the poultry industry) to assess their antimicrobial resistance resulting that all tested strains being multidrug-resistant. The obtained antimicrobial resistance index (AMRI) was 0.63 ± 0.07, a very high value. So, the alternative treatment seemed to be a valuable tool for R. anatipestifer control. Oregano nanoemulsion and its nanocomposite were characterized by TEM and the nano-size were 23.46 and 37.13 nm, respectively, and with a stable state, zeta potentials were 18.5 ± 5.11, 10.031 ± 5.11, the PDI were 0.236, 0.467 and IC50 is > 100 µg/ml and IC50 is 28.13 µg/ml, respectively). The study concluded that the tested R. anatipestifer strains are extensively multidrug-resistant and its control requires an alternative interference other than the antibiotics. Oregano- N-acetyl cysteine nanocomposite shows promising high activity against R. anatipestifer, which to be recommended.